1993
DOI: 10.1111/j.1346-8138.1993.tb01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical Aspects of the Oral Use of Retinoids in Acne

Abstract: A number of investigations of the effects of vitamin A deficiency in animals and man and its treatment with natural products containing vitamin A were carried out in the twenties and thirties. In 1942, a clinical study in patients with acne treated with vitamin A yielded encouraging results. Further trials in the forties and fifties, trying to confirm the beneficial effect of oral vitamin A in acne, met with equivocal success. In the sixties, all-trans retinoic acid (tretinoin) became clinically available, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In 1971, clinical trials' results revealed that isotretinoin was ineffective for treating skin cancer, but could be useful for the management of AV. However, due to concerns about its side effects and its potential to cause birth defects in particular, the medication was not released to the market until 1982 [ 19 ]. Isotretinoin is, by far, the most cost-effective drug when compared with other medications used for severe acne treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 1971, clinical trials' results revealed that isotretinoin was ineffective for treating skin cancer, but could be useful for the management of AV. However, due to concerns about its side effects and its potential to cause birth defects in particular, the medication was not released to the market until 1982 [ 19 ]. Isotretinoin is, by far, the most cost-effective drug when compared with other medications used for severe acne treatment.…”
Section: Discussionmentioning
confidence: 99%
“…53 The correlation of oral vitamin A and its therapeutic effects for AV was first shown in a clinical study in 1942. 54 This eventually became the basis for the development of tretinoin in the 1960s and isotretinoin in the 1970s. 5,54 It has also been observed that low levels of vitamin C are associated with poor wound healing and compensatory thickening of the stratum corneum.…”
Section: Diet and Metabolismmentioning
confidence: 99%
“…54 This eventually became the basis for the development of tretinoin in the 1960s and isotretinoin in the 1970s. 5,54 It has also been observed that low levels of vitamin C are associated with poor wound healing and compensatory thickening of the stratum corneum. 53 Taken together, these data suggest that appropriate levels of these and other vitamins and minerals could contribute to improving AV by supporting several of the important physiological mechanisms needed for healthy skin, with some observations more closely related to AV pathophysiology.…”
Section: Diet and Metabolismmentioning
confidence: 99%
“…The results of these trials were very encouraging. Daily doses between 5 and 20 mg given for 12 weeks resulted in good to excellent responses in about 80% of all cases including the severe cystic forms of acne' [327]. …”
Section: From Vitamin a To Isotretinoin: Innovative Views On Acne Patmentioning
confidence: 99%